Walking in two worlds: insights from implementing a Tr’ondëk Hwëch’in approach to bridging knowledge systems in conservation and land use planning - Chrystal Mantyka-Pringle; Jody Beaumont; Chris Clarke; Natasha Ayoub; Piia Kortsalo; Stephanie Saal; Katie Fraser; Kiri Staples; Tr’ondëk Hwëch’in (Ecology and Society)
Efforts to bring together Indigenous and Western science systems of knowledge have been ongoing for decades. In light of challenges related to knowledge integration, which have typically resulted in the favoring of Western knowledge systems at the expense of Indigenous knowledge, efforts to bridge these knowledges have expanded. Within such approaches, the two knowledge systems exist independently; one is not controlled or validated by the other. These efforts are especially critical within land use and conservation planning, which has often failed to include a broad range of Indigenous values, practices, and perspectives. We examine the extent to which two tools, including Indigenous land use and cultural mapping and a conservation prioritization software called Zonation, can be useful in bringing together Western scientific and Indigenous knowledge systems to inform conservation and land use planning. We look specifically at the experiences of Tr’ondëk Hwëch’in, a First Nation in the Yukon, northern Canada, and their approach of “walking in two worlds” within a regional land use planning process. We also explore how the conservation prioritization method and software, Zonation, can be modified with Indigenous cultural values and subsistence use areas. Our methodology aims to better understand the extent to which the software can be adapted to include other variations of bio-cultural attributes in partnerships with Indigenous peoples. We identified challenges, successes, and lessons learned within Tr’ondëk Hwëch’in’s approach, as well as insights for knowledge bridging efforts and land planning involving Indigenous authorities.